Hikmat Dalam Mengatur Perkataan: Studi Tematis Penggunaan Kata “Lidah” Dalam Kitab Amsal - Ragil Kristiawan; Aprilia Vrischilla Lumiling (Hymnos: Jurnal Teologi dan Keagamaan Kristen, 2024)
The book of Proverbs is a collection of wise sayings attributed to King Solomon as the wisest king in Israel. One of the themes taught in this book is about being wise in keeping words. The authors of the book of Proverbs often echo this theme with tongue allegations. This study aims to explore the teachings of the book of Proverbs regarding the use of the tongue by believers. The main question we want to discuss is: what is the teaching of Proverbs about wisdom in regulating words for social life? By using a literature study with topical methods, the truth about the use of tongues in this book of Proverbs is produced. The book of Proverbs warns about the dangers of speaking hastily or thoughtlessly, emphasizing the need for thoughtful and kind words. Negative words should be shunned by believers. On the other hand, positive words that slide out of the tongue give an indication of the existence of wisdom in a person's life. For Proverbs, life and death are actually influenced by the tongue. For those who can keep their words, they will gain life and success. On the contrary, for those who cannot keep their word, the destruction of life will be an inevitable certainty.